2006
DOI: 10.1002/bit.20935
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the stability of crosslinked protein crystals biotemplates: A feasibility study

Abstract: Protein crystals, routinely prepared for the elucidation of protein 3D structures by X-ray crystallography, present an ordered and highly accurate 3D array of protein molecules. Inherent to the 3D arrangement of the protein molecules in the crystal is a complementary 3D array of voids made of interconnected cavities and exhibiting highly ordered porosity. The permeability of the porosity of chemically crosslinked enzyme protein crystals to low molecular weight solutes, was used for enzyme mediated organic synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…2a) and the SeMet crystal diffracted to 7 Å resolution. To improve the diffraction, 5 ml of the cross-linking reagent glutaraldehyde was added to the 500 ml reservoir solution (Cohen-Hadar et al, 2006). Crystals were equilibrated at 293 K for 5 min, 10 min, 30 min, 2 h, 3 h and 4 h before being mounted on the loop.…”
Section: Diffraction Improvementmentioning
confidence: 99%
“…2a) and the SeMet crystal diffracted to 7 Å resolution. To improve the diffraction, 5 ml of the cross-linking reagent glutaraldehyde was added to the 500 ml reservoir solution (Cohen-Hadar et al, 2006). Crystals were equilibrated at 293 K for 5 min, 10 min, 30 min, 2 h, 3 h and 4 h before being mounted on the loop.…”
Section: Diffraction Improvementmentioning
confidence: 99%
“…Soon after, they demonstrated the enzymatic activity of GA cross‐linked carboxypeptidase‐A crystals in aqueous solutions different from that of the crystallization environment (Quiocho & Richards, ). Since then, aldehydes (Figure a), specifically GA, have been the dominant cross‐linking agents for the stabilization of protein crystals (Cohen‐Hadar et al, ; N. K. Khalaf et al, ; Yan et al, ). Despite the ubiquity of GA cross‐linking, the chemical basis is incompletely understood.…”
Section: Protein Crystalsmentioning
confidence: 99%
“…Protein crystals possess a three-dimensional ordered arrangement of protein molecules. 93 Cohen et al 94 dissolved CLPCs in aqueous ethylene glycol, induced polymerisation by the addition of ammonium persulfate, and then retrieved the crystals. Cvetkovic et al 91 investigated the transport of uorescein in lysozyme crystals by confocal laser scanning microscopy and found that the diffusion rate was highly related to the crystal structure.…”
Section: Applications Of Clpcsmentioning
confidence: 99%
“…Currently, the CLPCs have attracted a great deal of research interest as biological templates for the preparation of novel nano-structured composite materials. 94 Since then, the feasibility of using CLPCs as effective bio-templates for the construction of novel patterned composite materials has attracted pronounced attention.…”
Section: Applications Of Clpcsmentioning
confidence: 99%